(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The growing number of cancer survivors has brought increasing attention to the long-term effects of oncological diseases and the importance of post-treatment rehabilitation in improving quality of life. This study explores the role and effectiveness of rehabilitation therapies in enhancing the physical, psychological, and social well-being of individuals recovering from cancer. Drawing on recent clinical research and patient-reported outcomes, the paper evaluates various rehabilitation modalities, including physical therapy, psycho-oncological support, nutritional counseling, and occupational therapy. Findings indicate that structured and individualized rehabilitation programs significantly contribute to restoring functional capacity, reducing fatigue and depression, and facilitating social reintegration. Furthermore, multidisciplinary approaches tailored to the specific needs of cancer survivors yield better outcomes compared to generic treatments. The study underscores the necessity of integrating rehabilitation into standard oncological care pathways to ensure holistic recovery and sustained quality of life. Future research should focus on long-term effectiveness, accessibility, and patient-centered program design.